Effect of transportation and storage time on the frozen lamb quality in catering sector - Sad, Fadi; Rozalli, Norazatul Hanim Mohd (Journal of Food Technology Research, 2025)
Ensuring the quality and safety of frozen lamb during transportation and storage is critical to preventing foodborne illnesses and maintaining product quality. Cold chain logistics (CCL) are essential for keeping meat fresh and safe, but long transportation times or unstable temperatures can lead to spoilage. This study evaluated the effects of transportation time and temperature variation within the CCL on the microbial and physicochemical quality of frozen lamb used in catering services in the UAE. Lamb samples were subjected to transport durations of 30, 45, and 90 minutes, followed by storage at -18°C for 30 days. Physicochemical analyses (pH, fat content, Total Volatile Basic Nitrogen (TVBN), and colour) and microbiological analysis (Total Viable Count (TVC)) were conducted at 10, 20, and 30-day intervals. Results showed that shorter transport times and stable storage conditions helped preserve quality, while extended durations led to significant spoilage. Longer handling periods (90 minutes of transportation and 30 days of storage) resulted in higher TVC, increasing from an initial 510 CFU/g to 8266 CFU/g, along with increased pH, fat content, and TVBN, indicating microbial growth and spoilage. Interestingly, colour remained stable throughout the storage period. These findings highlight the importance of maintaining strict temperature control during frozen meat transportation to ensure food safety and product quality.